PERFORMANCE COMPARISON OF MULTICELL SERIES AND NPC MULTILEVEL CONVERTERS FOR A STATCOM - Belakehal, S.; Djellad, A.; Chenni, R. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2019)
Abstract. In this paper, we present a comparative study of the performances of the multicells series and the Neutral-Point-Clamped (NPC) three-level converters used at synchronous static compensators (STATCOM) for the control of the voltage at a point of the network. The analysis consists on a mathematical modeling, a pulse width modulation (PWM) control algorithm application and a simulation using the Matlab Simulink environment. The simulation results obtained show that the STATCOM allows the regulation of the voltage at the point of common coupling (PCC) by acting the reactive energy that it can supply or absorb.